« Ma maman elle a parlé de ça ? » Retour sur une recherche biographique auprès d’enfants de six à onze ans après une intervention sociale - Claire Ganne (Sociétés et Jeunesses en Difficulté)
Growing interest in biographical research and research involving children leads us to investigate the possibility to conduct biographical interviews with children. Is it relevant to conduct research interviews with six to eleven years old children, especially after social interventions? Are they able to produce biographical narratives and to regulate the interaction with an adult? How do they use their sense of agency during the interview? This article is based on qualitative interviews with twenty-two children (6-11 years old). These children had all been housed in shelter for single mothers with infants during their first years of life, but have experienced various trajectories after leaving the shelter. The findings emphasize the importance of the relationship with the adults and the perception of their own agency to understand the involvement of children in biographical narratives, regardless of their age.